2021
DOI: 10.1007/s00784-020-03768-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short-fiber composite base on fracture behavior of direct and indirect restorations

Abstract: Objectives The aim was to examine the influence of short-fiber composite (SFC) core on the fracture-behavior of different types of indirect posterior restorations. In addition, the effect of thickness ratio of SFC-core to the thickness of the veneering conventional composite (PFC) on fracture-behavior of bi-structured composite restorations was evaluated. Materials and methods MOD cavities with removed palatal cusps were prepared on 90 intact molars. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
24
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 37 publications
(52 reference statements)
7
24
0
3
Order By: Relevance
“…Our results show the superiority of bi-structured direct restorations over conventional composite fillings when tested with extremely high forces. This is in line with other studies [ 26 , 28 ]. Our results also suggest that the consistency (highly filled flowable or conventional packable) of the occlusally placed composite is not a significant factor in the fracture resistance of a direct restoration utilizing flowable SFRC.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results show the superiority of bi-structured direct restorations over conventional composite fillings when tested with extremely high forces. This is in line with other studies [ 26 , 28 ]. Our results also suggest that the consistency (highly filled flowable or conventional packable) of the occlusally placed composite is not a significant factor in the fracture resistance of a direct restoration utilizing flowable SFRC.…”
Section: Discussionsupporting
confidence: 94%
“…In the static load-to-fracture test, all bi-structured restorations (SFRC + conventional composite coverage), irrespective of the application mode of flowable SFRC or the consistency of the occlusal composite material, showed significantly higher fracture toughness in comparison to the control group (conventional composite filling). This is in accordance with the findings of Garoushi et al, where flowable SFRC covered with a minimal amount of composite showed significantly higher fracture resistance compared to conventional composite filling [28]. However, in that study the cavities were larger than those seen in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Short fiber-reinforced core composites, on the other hand, showed the ability to re-direct and stop crack propagation within the materials [31]. The presence of such energyabsorbing and stress-distributing fibers allows crack propagation to be deflected away from the bulk of the material and toward the peripheries [62][63][64].…”
mentioning
confidence: 99%
“…Therefore, the second null hypothesis was accepted. It is clearly shown in the literature that the brittleness of the conventional PFC materials generates bulk fracture propagating easily through the whole thickness of the restoration, reaching the tooth substance to be propagated further [62,63]. Thus, the basic characteristics of the PFC materials do not offer significant protection against fatigue crack propagation.…”
mentioning
confidence: 99%